Silip sa nakasarang pinto ni dyoker: a phenomenological study on Filipino stand-up comedians - Jim Jandro P. Tolentino et.al. 4 0 16; 5 (2017)
ABSTRACT: Stand-up comedians are performers who present comedic acts onstage. They make it look easy and the common concept that people have about them is that they are the jolliest and optimistic persons in the world but in reality, being a stand-up comedian is a lot of hard work. This study focused on the lived experiences of the Filipino stand-up comedians with the use of descriptive phenomenological analysis. The participants were chosen through purposive and snowball sampling from the three selected comedy bars with the criteria of 3 years of experience as a comedian regardless of age and gender. The researchers conducted a semi structured interview with each of the participants and the discussions were transcribed for further analysis. The transcripts were thoroughly read and the researchers identified emerging themes from the responses which were clustered into subordinate themes. To validate and determine the data saturation, the researchers applied consensus between researchers and validation interview. The results showed that most of the stand-up comedians were influenced by their peers in selecting this career, still experienced anxiousness in performing but chose to continue for it aids them financially and fulfils their passion in entertaining people.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2